Load Balancing in Cloud Computing using Honey Bee Swarm Intelligence Technique - et al., Vrajesh Sharma (International Journal of Control and Automation, 2019)
In cloud computing, job scheduling is one of the prominent research areas. Many endeavors have been made to provide efficient scheduling algorithms for optimizing the utilization of resources in cloud computing. It has been observed while scheduling in real time scenario, the system gets overloaded and the performance declines and compromises at the Quality of Service (QoS). Therefore some efficient load balancing technique is required to be deployed at the intra-datacenter level to prevent the system from violating the Service level agreement (SLA). Many swarm intelligence techniques have been rendered and studied in the previous year’s which provide an intelligent insight for balancing the load on the system. In this paper Honey Bee foraging behavior inspired algorithm has been studied/presented to balance the load on the system, to ensure the optimal utilization of resources and to improve QoS in cloud computing environment.